PALEOMAGNETISM OF DEVONIAN ROCKS IN THE OL'DOI TERRANE, UPPER AMUR REGION - Kravchinsky V.A.; Sorokin A.A. (My University, 2001)
Deformed thick Paleozoic sequences of the Ol’doi Terrane, sublatitudinally extended along the northern margin of the Amur Superterrane, are considered as fragments of a passive continental margin [2, 4]. To the north, along fault zones incorporated into the South Tukuringra Fault System, they are conjugated with predominantly oceanic formations of the eastern segment of the Mongol–Okhotsk Foldbelt (Fig. 1). In the present work, we first present paleomagnetic poles for Devonian deposits of the Ol’doi Terrane, which are evidence for the significant width of the Mongol–Okhotsk Paleoocean.
Keywords: Devonian; Ol’doi Terrane; Amur Superterrane; Paleozoic::Devonian; Палеозой::Девонская